2019
DOI: 10.1002/dc.24358
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of preoperative pancreatic biopsy, cytological/histological review of cell‐block‐specimens obtained by endoscopic ultrasound‐guided fine‐needle aspiration: Laboratory‐based study

Abstract: Background Pancreatic cancer is among the most lethal cancers worldwide due to the limited availability of techniques for early detection of signs and symptoms. Reportedly, it is the fourth‐leading cause of cancer‐related mortality among Japanese adults. With the advent of endoscopic ultrasound‐guided fine‐needle aspiration (EUS‐FNA) for diagnosing pancreatic cancer, the rate of the cytological and histological diagnoses of cell‐block‐specimens has significantly increased in Japan. Methods The cytological spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…The reason for this may be the intervention of the cytopathologist/ pathologist/ cytology technician who qualifies the cytological material as insufficient during ROSE, increasing the number of passes and the manipulation for obtaining tissue, also spreading the tissue to the slides and forming the appropriate cell block. The advantages of obtaining a cell block, especially with fine needle aspiration, are: being able to see the lesion pattern, performing immunohistochemical staining to support the diagnosis, and acquirement of tissue for molecular analysis, even contributing to the appropriate chemotherapy regimen and molecular targeted therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason for this may be the intervention of the cytopathologist/ pathologist/ cytology technician who qualifies the cytological material as insufficient during ROSE, increasing the number of passes and the manipulation for obtaining tissue, also spreading the tissue to the slides and forming the appropriate cell block. The advantages of obtaining a cell block, especially with fine needle aspiration, are: being able to see the lesion pattern, performing immunohistochemical staining to support the diagnosis, and acquirement of tissue for molecular analysis, even contributing to the appropriate chemotherapy regimen and molecular targeted therapy [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chung et al in their multicenter study, suggested 4 as the optimum number of passes to be applied in centers that do not use ROSE in Korea [ 5 ]. Mizutani et al demonstrated the contribution of the cell block acquirement to make the definitive diagnosis, in terms of the applicability of ancillary tests and molecular studies [ 19 ]. Therefore, even a single cell block from the lesion can be very valuable, increasing the sensitivity and specificity for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this may be the intervention of the cytopathologist/ pathologist/ cytology technician who quali es the cytological material that is insu cient during ROSE, increasing the number of passes and the manipulation for obtaining tissue, also spreading the tissue to the slides and forming the appropriate cell block. The advantages of obtaining a cell block, especially with ne needle aspiration, are being able to see the lesion pattern, performing immunohistochemical staining to support the diagnosis, and acquirement of tissue for molecular analysis, even contributing to the chemotherapy regimen and molecular target therapy [19].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Chung et al in their multicenter study, they suggested 4 as the optimum number of passes to be applied in centers that do not use ROSE in Korea [5]. Mizutani et al demonstrated the contribution of the cell block acquirement in their study to make the de nitive diagnosis, in terms of the applicability of ancillary tests and molecular studies [19]. Therefore, even a single cell block from the lesion can be very valuable, increasing the sensitivity and speci city for accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some hospital facilities, cytological examinations and tissue biopsies are performed together. As the author noted [21], both tests have their own advantages and disadvantages. Unlike tissue biopsy, cytology allows specimens to be obtained from background findings.…”
Section: Standard Correct Methods Of Fine Needle Aspiration Cytology ...mentioning
confidence: 99%